Transitioning Focus Group Research to a Videoconferencing Environment: A Descriptive Analysis of Interactivity - Cristine B. Henage; Stefanie P. Ferreri; Courtney Schlusser; Tamera D. Hughes; Lori T. Armistead; Casey J. Kelley; Joshua D. Niznik; Jan Busby-Whitehead; Ellen Roberts (MDPI AG, 2021)
The COVID-19 pandemic disrupted face-to-face interactions in healthcare research, with many studies shifting to video-based data collection for qualitative research. This study describes the interactivity achieved in a videoconferencing focus group of seven primary care providers discussing deprescribing opioids and benzodiazepines. Researchers reviewed video footage of a focus group conducted via Zoom and assessed interactivity using Morgan's framework for focus group communication processes. Two reviewers categorized the type of exchanges as sharing information, comparing experiences, organizing, and conceptualizing the content, as well as validating each other or galvanizing the discussion with "lightning strike" ideas. The conversation dynamics in this focus group included clear examples of interactivity in each of the categories proposed by Morgan (validating, sharing, comparing, organizing, conceptualizing, and lightning strikes) that were observed by two different reviewers with demonstrated high interrater reliability. Conducting focus groups with a skilled moderator using videoconferencing platforms with primary care providers is a viable option that produces sufficient levels of interaction.